2014
DOI: 10.1055/s-0034-1387816
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining Success of Awake and Asleep Magnetic Resonance Imaging Scans in Nonsedated Children

Abstract: Effective techniques that allow children to complete magnetic resonance imaging (MRI) scans without sedation are high priority for the imaging community. We used behavioral approaches to scan 64 sleeping infants and toddlers younger than 4 years, and 156 awake children aged 2.5 to 18 years, for a neuroimaging research protocol. Infants and their families participated in a desensitization protocol for several days, then scanning was performed at the child's bedtime during natural sleep. For awake young children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…We probed language networks using a well-characterized task (Karunanayaka et al 2007; Schmithorst et al 2006): passively listening to stories (Story Listening Task). Given the similar (though attenuated) brain activation patterns we observed in the sleeping infants relative to our previous studies in sleeping (Merhar et al 2016; Vannest et al 2014; Wilke et al 2003), sedated (Patel et al 2007; Holland et al 2004; DiFrancesco et al 2013) and awake children (Szaflarski et al 2012; Karunanayaka et al 2007; Vannest et al 2009; Holland et al 2007) using this task, we have a good measure of confidence that the BOLD effect is somewhat preserved in the sleeping infant cohorts studied here. Similar arguments apply to our assessment of sensory motor function in this study.…”
Section: Methodssupporting
confidence: 78%
See 1 more Smart Citation
“…We probed language networks using a well-characterized task (Karunanayaka et al 2007; Schmithorst et al 2006): passively listening to stories (Story Listening Task). Given the similar (though attenuated) brain activation patterns we observed in the sleeping infants relative to our previous studies in sleeping (Merhar et al 2016; Vannest et al 2014; Wilke et al 2003), sedated (Patel et al 2007; Holland et al 2004; DiFrancesco et al 2013) and awake children (Szaflarski et al 2012; Karunanayaka et al 2007; Vannest et al 2009; Holland et al 2007) using this task, we have a good measure of confidence that the BOLD effect is somewhat preserved in the sleeping infant cohorts studied here. Similar arguments apply to our assessment of sensory motor function in this study.…”
Section: Methodssupporting
confidence: 78%
“…Inducing and maintaining natural sleep is a challenging element to add to any imaging experimental protocol. Nevertheless, development of these protocols has taken place at a few sites, including ours (Dehaene-Lambertz et al 2002; Anderson et al 2001; Redcay et al 2007; Vannest et al 2014). Previous work in our laboratory demonstrates that fMRI is capable of imaging the status of auditory cortex and subsequent processing in response to sound stimulation (Holland et al 2004; Patel et al 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Implementation of behavioral interventions promoting nonsedated MRI scans has been reported [1, 2, 3, 4, 6, 11, 12, 13, 16, 17, 18, 19, 20, 21, 22, 23] and studies have demonstrated success at promoting nonsedated MRI scans [13, 14, 25, 29]. However, our study is the first to systematically evaluate parental acceptance and preferences for strategies to promote nonsedated MRI scans in children with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, this depends on the individual child. Actually, as young as 2-year-old children have been successfully scanned awake using progressive behavioral training method ( Vannest et al, 2014 ). This training procedure was limited to 15 min and contained 3 steps: first children were asked to sit on the scanner bed, then to lie down, and then to hold “still as a statue”.…”
Section: Discussionmentioning
confidence: 99%